Estimation of polluting emissions from mobile sources in the mining city of Pasco using the IVE model - Hilario Román, Nilda (2011)
This study shows the estimates of emissions from mobile sources in the districts of Chaupimarca, Yanacancha and Simón Bolívar, in the Province and Department of Pasco. The methodology is based on the International IVE Model that estimates atmospheric pollutants based on three components such as: 1) Emission factors, 2) Vehicle activity, and 3) Distribution of the vehicle fleet. It was necessary to collect data from the vehicle fleet in the mentioned area to quantify the components and thus obtain an emissions inventory. The results of the emission of pollutants are as follows: CO is 24 047.31 Kg / day, NOX is 2 309.49 Kg / day, VOC is 1 602.19 Kg / day, SOX is 119.76 Kg / day and PM is 32.81 Kg / day, for a vehicular population of 4,500 units and an average travel magnitude of 527,362 km. In conclusion, mobile sources emit 28.11 MT / day of atmospheric pollutants and CO is considered the pollutant that is emitted in the greatest quantity with an average of 24.05 MT / day, or an average daily emission rate of 45 g / Km traveled, and the main source is Station Wagon vehicles that emit 18 649.52 Kg / day. At a height of 4349 masl, there is a pressure of 331.75 mm Hg and with the high presence of polluting emissions of CO, NOX and VOC due to incomplete combustion in vehicles that mostly use 90 octane gasoline, mainly humans The vulnerable population can be affected their airways in a dramatic way, due to the greater effort they make in the breathing process, causing the entry of polluting agents into their body. As altitude increases, oxygen pressure decreases.